Product Originality and Buying Culture on Purchase Decisions Through Brand Advocacy on JD.ID E-Commerce - Pranata, Sungguh (Cebong Journal, 2023)
The main objective of this research is to analyze the effect of product orientation and buying culture on purchasing decisions through brand advocacy in JD.ID E-Commerce. The approach used in this research is associative and quantitative by using path analysis. The population in this study are friends, family and all those related to social media Facebook and the researcher's TikTok. The time of the research was conducted from April 2023 to May 2023. Where the sample in this study was 119 respondents. The results showed that the color of the product on the purchasing decision of the t test results was 0.749 < t table 1.196 and the original sample was 0.471, the P-Value was 0.015. For buying culture on buying decisions, the results of the t test from this study were 1.764 > ttable 1.196 and the initial sample was 0.167 with a P-Value of 0.004. To differentiate products through brand advocacy on purchasing decisions, the t test is 0.925 < t table 1.196 and the original sample is 0.332 with a P-Value of 0.012. And for the buying culture variable through brand advocacy on purchasing decisions. of 3.765 > ttable 1.196 and the original sample is 0.351 with a P-Value of 0.005